Reflexivity as a personal resource of future teachers (Gumilyov Journal of Pedagogy, 2025)
The study of reflexivity as a personal resource for future educators is the focus of this article. The study presents the notions of reflexivity and reflection, and it outlines the significance of reflexivity for a prospective teacher's career. The findings of A.V. Karpov's survey, which assessed the reflexivity of prospective instructors at L.N. Gumilyov Eurasian National University, are reported.There is a connection between the levels of reflection that are common among young teachers and their level of reflexivity. The writers of the paper assessed how much future teachers' reflexivity is developing and examined the state of affairs.  The authors carried out the diagnostics of reflexivity survey, which was intended to gauge the level of development of a trait as personal as reflexivity. The research technique is based on the analysis and generalization of the works of foreign experts on this topic, which identifies the main ideas and definitions. The article also takes into account the unique qualities of reflexivity as a personal tool for future teachers. The findings of this research demonstrate that students' reflexivity levels range from moderate to high and there are subtleties to take into account regarding the degree of reflexivity. While a large percentage of students acknowledge that they occasionally act impulsively and make careless choices, many also reflect carefully about their actions and how they affect other people.